Pharmacological Activation of Rev-erbα Attenuates Doxorubicin-Induced Cardiotoxicity by PGC-1α Signaling Pathway - Runmei Zou; Shuo Wang; Hong Cai; Yuwen Wang; Cheng Wang (Hindawi-Wiley, 2023)
Background. Doxorubicin-induced cardiotoxicity has been closely concerned in clinical practice. Rev-erbα is a transcriptional repressor that emerges as a drug target for heart diseases recently. This study is aimed at investigating the role and mechanism of Rev-erbα in doxorubicin-induced cardiotoxicity. Methods. H9c2 cells were treated with 1.5 μM doxorubicin, and C57BL/6 mice were treated with a 20 mg/kg cumulative dose of doxorubicin to construct doxorubicin-induced cardiotoxicity models in vitro and in vivo. Agonist SR9009 was used to activate Rev-erbα. PGC-1α expression level was downregulated by specific siRNA in H9c2 cells. Cell apoptosis, cardiomyocyte morphology, mitochondrial function, oxidative stress, and signaling pathways were measured. Results. SR9009 alleviated doxorubicin-induced cell apoptosis, morphological disorder, mitochondrial dysfunction, and oxidative stress in H9c2 cells and C57BL/6 mice. Meanwhile, PGC-1α and downstream signaling NRF1, TAFM, and UCP2 expression levels were preserved by SR9009 in doxorubicin-treated cardiomyocytes in vitro and in vivo. When downregulating PGC-1α expression level by specific siRNA, the protective role of SR9009 in doxorubicin-treated cardiomyocytes was attenuated with increased cell apoptosis, mitochondrial dysfunction, and oxidative stress. Conclusion. Pharmacological activation of Rev-erbα by SR9009 could attenuate doxorubicin-induced cardiotoxicity through preservation of mitochondrial function and alleviation of apoptosis and oxidative stress. The mechanism is associated with the activation of PGC-1α signaling pathways, suggesting that PGC-1α signaling is a mechanism for the protective effect of Rev-erbα against doxorubicin-induced cardiotoxicity.